Impact of Type 2 Myocardial Infarction (MI) on Hospital‐Level MI Outcomes: Implications for Quality and Public Reporting - Sameer Arora; Paula D. Strassle; Arman Qamar; Evan N. Wheeler; Alexandra L. Levine; Jacob A. Misenheimer; Matthew A. Cavender; George A. Stouffer; Prashant Kaul (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
BackgroundThe International Classification of Diseases (ICD) coding system does not recognize type 2 myocardial infarction (MI) as a separate entity; therefore, patients with type 2 MI continue to be categorized under the general umbrella of non–ST‐segment–elevation myocardial infarction (NSTEMI). We aim to evaluate the impact of type 2 MI on hospital‐level NSTEMI metrics and discuss the implications for quality and public reporting. Methods and ResultsWe conducted a single‐center retrospective analysis of 1318 patients discharged with a diagnosis of NSTEMI between July 2013 and October 2014. The Third Universal Definition was used to define type 1 and type 2 MI. Weighted Kaplan–Meier curves were used to analyze risk of mortality and readmission. Overall, 1039 patients met NSTEMI criteria per the Third Universal Definition; of those, 264 (25.4%) had type 2 MI. Patients with type 2 MI were older, were more likely to have chronic kidney disease, and had lower peak troponin levels. Compared with type 1 MI patients, those with type 2 MI had higher inpatient mortality (17.4% versus 4.7%, P<0.0001) and were more likely to die from noncardiovascular causes (71.7% versus 25.0%, P<0.0001). Despite weighting for patient characteristics and discharge medications, patients with type 2 MI had higher mortality at both 30 days (risk ratio: 3.63; 95% confidence interval, 1.67–7.88) and 1 year (risk ratio: 1.98; 95% confidence interval, 1.44–2.73) after discharge. Type 2 MI was also associated with a lower 30‐day cardiovascular‐related readmission (risk ratio: 0.49; 95% confidence interval, 0.12–2.06). ConclusionsNSTEMI metrics are significantly affected by type 2 MI patients. Type 2 MI patients have distinct etiologies, are managed differently, and have higher mortality compared with patients with type 1 MI. Moving forward, it may be appropriate to exclude type 2 MI data from NSTEMI quality metrics.